(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The advent and rapid unfold of excessive yielding varieties within the late 20s and early 21s ended in consistent output boom for meals vegetation in India. District wise fashion in vicinity, manufacturing and productivity have tested on this paper. To analyzed the traits linear regression has been used to check the charge of change. As well as for significance student t check statistics has been used. The correlation in between place and production also tested from 2001-2022.The analysis discovered that boom of the production at macro level is specifically yield led because of development and unfold of high yield varieties and generation intervention. This paper seeks to study the nature and volume of inter-district version inside the growth of area, manufacturing and productivity of major vegetation over the have a look at duration from 2001 – 2022